Parts of medical terms derived from Latin and their importance in medical communication - Tuychieva , Odina (The Lingua Spectrum, 2025)
The Latin language, once the official language of the Roman Empire, now plays a crucial role in fields such as medicine, science, and law due to its historical and scientific significance. This article discusses Latin’s relevance in creating clear, precise terminology for medical and scientific communication, where it serves as a foundation for universal understanding. From the biological naming system developed by Carl Linnaeus to terms used in chemistry and pharmacology, Latin ensures consistent communication among international experts. The text also highlights Latin’s role in preserving cultural heritage, with many ancient texts forming the backbone of modern scientific knowledge.